Batik Recognition and Classification Using Transfer Learning and MobileNet Approach - Sastypratiwi, Helen; Muhardi, Hafiz; Yulianti, Yulianti (Society of Visual Informatics, 2024)
In the vibrant tapestry of Indonesian culture, Batik motifs stand out as a testament to its enduring artistic heritage. Yet, adapting these intricate patterns, particularly the mesmerizing